2016
DOI: 10.1534/genetics.115.183533
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interplay of Two Paralogs Encoding SWI/SNF Chromatin-Remodeling Accessory Subunits DuringCaenorhabditis elegansDevelopment

Abstract: SWI/SNF ATP-dependent chromatin-remodeling complexes have been related to several cellular processes such as transcription, regulation of chromosomal stability, and DNA repair. The Caenorhabditis elegans gene ham-3 (also known as swsn-2.1) and its paralog swsn-2.2 encode accessory subunits of SWI/SNF complexes. Using RNA interference (RNAi) assays and diverse alleles we investigated whether ham-3 and swsn-2.2 have different functions during C. elegans development since they encode proteins that are probably mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…MEL-28 strongly accumulated on condensed oocyte chromosomes ( S1C Fig ; [ 9 , 18 ]). Moreover, we noted during our initial studies of mel-28 mutant or RNAi-treated embryos that formation and migration of the maternal pronucleus was often more severely affected than the paternal pronucleus [ 9 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…MEL-28 strongly accumulated on condensed oocyte chromosomes ( S1C Fig ; [ 9 , 18 ]). Moreover, we noted during our initial studies of mel-28 mutant or RNAi-treated embryos that formation and migration of the maternal pronucleus was often more severely affected than the paternal pronucleus [ 9 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data presented here provide functional and mechanistic evidence for the long-standing visual correlation between NPCs and open chromatin and validates the hypothesized relationship between them. Interestingly, previous genetic and proteomic experiments have reported interactions between the Caenorhabditis elegans homologue of Elys, MEL-28, and chromatin-remodeling complexes, including the SWI/SNF complex subunit SWSN-2.2 ( Fernandez et al, 2014 ; Ertl et al, 2016 ), suggesting an evolutionarily conserved role for Elys in regulating chromatin state. Furthermore, genetic and physical interactions between yeast NPC components and the chromatin-remodeling RSC complex have also been reported ( Titus et al, 2010 ; Van de Vosse et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…When we compared the list of 53 high confidence candidate AKIR-1 binding proteins with the 190 proteins identified as potential interactors of the nematode BAP60 homologue SWSN-2.2 (Ertl, Porta-de-la-Riva et al, 2016), we found only 3 common proteins, none of which have been characterized as being specific regulators of nlp-29p::gfp expression (i.e. found as Nipi genes (Zugasti et al, 2016); Table S2).…”
Section: Akir-1 Forms a Complex With Components Of The Nurd And Mec Cmentioning
confidence: 99%
“…This suggests that in some contexts, but not during its regulation of AMP gene expression, AKIR-1 might interact with the SWI/SNF complex. This functional dichotomy was further reinforced by examining the genes differentially regulated following knockdown of swsn-2.2 and its paralogue ham-3 (Ertl et al, 2016). There were only a very small number (28/1468) of genes characterized as up-regulated by D. coniospora infection and among them, there were none encoding AMPs (JJE unpublished observations).…”
Section: Akir-1 Forms a Complex With Components Of The Nurd And Mec Cmentioning
confidence: 99%
See 1 more Smart Citation